As condições de trabalho dos professores em escolas do/no campo: análise dos municípios da microrregião de Prudentópolis – PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
This Doctoral dissertation has as main objective to analyze the working conditions of teachers in schools of/in the rural area of the Municipal Education Network in the municipalities of the Prudentópolis micro-region, in the state of Paraná, Brazil. The municipalities that make up this micro-region are: Fernandes Pinheiro, Guamiranga, Imbituva, Ipiranga, Ivaí, Prudentópolis and Teixeira Soares. Based on the historical and dialectical materialism, a bibliographic and documentary study and questionnaires were carried out. Initially, a discussion was held on the relationships between the new morphology of work in the capitalist society and the teaching valorization policies in Brazil, starting from the ontological constitution of work and its consequences in its subsequent forms of being, in the capitalist society, to understand its impact on the educational field and teaching practice. The exposition also includes an analysis of teacher valorization policies in Brazil and statistical data; the documentary analysis of laws and normative acts that deal with teacher valorization and Rural Education policies and the analysis of the career plans of teachers in the Municipal Education Network in the micro-region of Prudentópolis. The investigation was carried out in municipal schools of/in the rural area of these municipalities, through questionnaires aimed at teachers, via Google Forms, and through the Municipal Department of Education of each municipality. The study identified that, in a historical-social process, schools of/in the rural area continue between precarious working conditions and the dismantling of schools. It is, on the one hand, the denial of the right to education to rural subjects and, on the other, the institutionalization of a new precariousness of work, typical of flexible accumulation. Rural workers, made invisible by public authorities, have their rights denied or achieved in a partial and fragmented way, and the same happens with teachers who work in this context. The schools that resisted in the rural area are a space for overworked professionals, whose work goes beyond the development of pedagogical activities, and also administrative and general services, operating with a precarious infrastructure, with few professionals and limited resources. Working conditions, which are decisive for teachers to continue teaching in the rural area, are treated in a tangential and generic way in education policies, remaining invisible in municipal career plans and in the materiality of the objective reality. The regulations that deal with the working conditions of rural teachers, in their career plans, are limited to a derisory bonus for traveling and teaching in multigrade schools, highlighting a situation of devaluation, considering the specificities of the work they carry out. Teaching praxis in the rural area preserves its original forms of precariousness and multifunctionality, with inadequate working conditions, following a direction diametrically opposed to that of teaching valorization, generating impacts on the working conditions of teachers of/in the rural area, especially in intensification, precariousness and in the deregulation of working hours. Opposing this process of dismantling rural schools, resistance processes are created. In spite of the inadequate working conditions, there is a struggle movement conducted by many teachers who work in these institutions to keep rural schools.
Keywords: Condições de trabalho dos professores; Educação do campo; Escolas rurais; Política educacional; Redes municipais; Teachers’ working conditions; Rural education; Rural schools; Education policy; Municipal networks; CNPQ::CIENCIAS HUMANAS::EDUCACAO